A Green Product Using Selective Compound for Susceptible Assessment of Copper in Blood Serum - Kirem, Hussain; Abdulhasan Naser*, Naser (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
A highly reliable approach for assessment of copper(II) in blood serum samples using an organic molecule 4-(3-hydroxyphenylazo)resorcinol, 4-HAR was developed. The paper presents the synthesis of 4-HAR, which serves as probe for definite species. 4-HAR was characterized with the FT-IR, UV-visible, 1H-NMR, 13C-NMR and mass analysis, thermal TG and DSC techniques. After examining its interactions with more than twenty-five metal ions, it was found that 4-HAR showed reaction only with copper(II), giving a distinct green color at λmax 603 nm. Experimental conditions for the reaction of 4-HAR with copper(II) were optimized. A calibration curve was created and the exhibition range of concentration obeyed Beer's Law from 0.30 to 16 μg.mL-1 with correlation coefficient of r = 0.9986, and value of the molar absorption coefficient, ε, being 3314 L.mol- 1.cm-1. The analytical method was used to determine copper(II) levels in several blood serum samples. The amounts of copper(II) found in the sera samples were compared with flame atomic absorption spectrometry technique, and the results were found to be highly reliable. Based on validation, the new approach can be utilized for assurance quality purposes with a high degree of confidence. Keywords: blood serum; copper(II); assessment; resorcinol; solvatochromism; spectrophotometry *Corresponding author: Tel.: (+96)7802424994 E-mail: nasir.almutawiri@uokufa.edu.iq